The Role of DPRD Supervision in Increasing the Effectiveness of APBD Use for Regional Development in Deli Serdang Regency - Marpaung, Mangadar; Siregar, Akbar; Ihsan Effendi (International Forum of Researchers and Lecturers, 2024)
The administration of government in Indonesia is based on a systemic approach which includes a central government system, called the government, as well as a regional government system. In the practice of government administration, there are concepts of centralization and decentralization that regulate the relationship between central and regional governments. The concept of centralization reflects the characteristic where all authority for administering government is centered in the central government, while the concept of decentralization shows the characteristic where some authority for government affairs, which was previously the responsibility of the central government, is delegated to regional governments . According to Law Number 23 of 2014 concerning Regional Government, the Regional People's Representative Council (DPRD) has a clear position as an integral regional people's representative institution in the administration of government at the local level. DPRD is not just a representative institution, but is also an inseparable part of the regional government structure. The function of the DPRD includes three main aspects, namely legislation, budgeting and supervision. (Kasenda et al., 2020). In an effort to realize this target, the Regional People's Representative Council (DPRD) needs to take concrete steps that can optimally strengthen its role in the context of regional government. The APBD is the implementation of the people's wishes for the government through the DPRD to improve welfare and services to the community. APBD is also the regional government's annual financial planning which is approved by the DPRD and made into policy through regional regulations. As a legislative institution, the DPRD has the responsibility to supervise the use of the budget and the implementation of regional government programs. Effective supervision is expected to increase transparency, accountability, and ensure that the benefits of the programs designed are truly felt by the community, especially those who need it most. Based on this description, the author is interested in conducting further research on the function of the Deli Serdang Regency DPRD in implementing the Regional Revenue and Expenditure Budget in the Development Sector. In formulating regional government policies, both from the executive and legislative branches, the orientation is to pay attention to the welfare of the people. Based on the results of the analysis and discussion, the conclusion is that direct supervision has a positive and significant effect on the effectiveness of supervision. Direct supervision has a positive and significant effect on APBD implementation. Indirect supervision has a positive and significant effect on the effectiveness of supervision. Indirect supervision has a positive and significant effect on APBD implementation. The effectiveness of supervision has a positive and significant effect on APBD implementation. Direct supervision has a positive and significant effect on APBD implementation through the effectiveness of supervision. Indirect supervision has a positive and significant effect on APBD implementation through the effectiveness of supervision.